VD_FINDINFO ML / 2015 / 58 vom 17. März 2015 - VD Tribunal cantonal (2015)
SOLIDARITÉ PASSIVE, CAUTIONNEMENT, FORME AUTHENTIQUE, NULLITÉ, MAINLEVÉE PROVISOIRE, COBAILLEUR | 143 al. 1 CO, 143 CO, 492 CO, 82 al. 1 LP